32. SURVEY OF KNOWLEDGE AND ATTITUDE OF NURSES IN THE DEPARTMENT OF ANESTHESIOLOGY AND RESUSCITATION, EYE HOSPITAL OF HO CHI MINH CITY ON THE IMPLEMENTATION OF THE SURGICAL SAFETY CHECKLIST (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the knowledge and attitude among preoperative nurses regarding implementing the surgical safety checklist as well as associated factors.Method: A descriptive cross-sectional study was conducted on 93 perioperative nurses at Department of Anesthesiology and Resuscitation, Eye Hospital of Ho Chi Minh city from October 2023 to April 2024.Results: The study found that the average age of the nurses participating in the study was 38.51 years; the majority of nurses were female (58.1%); and university level was the majority at 55.9%. The study found that 54.8% of nurses had good knowledge, 40.9% of nurses had average knowledge. 81.7% of nurses had a positive attitude towards implementing the surgical safety checklist. Educational level and clinical work experience are associated factors of nurses’ knowledge and attitude regarding the surgical safety checklist.Conclusions: The study noted that nurses still lacked knowledge and had negative attitudes toward implementing the surgical safety checklist. Training should be organized to improve nurses' knowledge and attitudes toward implementing the surgical safety checklist and to strengthen monitoring and evaluation of compliance with the use of the surgical safety checklist.
Keywords: Surgical safety checklist; preoperative nurses; knowledge; attitude